2006
DOI: 10.1039/b600250c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorption and diffusion on Pt {111} and PtSn {111}

Abstract: PtSn {111} forms two ordered surface alloys namely p(2 6 2) and (!3 6 !3R30u) and such bimetallic catalysts are often used in industrially catalysed reactions, such as hydrogenations, to improve performance although the reasons behind the improvements are generally not well understood. In this study density functional theory calculations have been performed for hydrogen adsorption at various sites on Pt {111} and the ordered PtSn {111} surfaces in order to characterise the differences between the pure and dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 29 publications
7
47
0
1
Order By: Relevance
“…5a. According with Langmuir's isotherm an exponent n equal to 2 indicates that the adsorption of hydrogen is dissociative (i), which is consistent with studies of the hydrogen adsorption on Pt surfaces in dry atmospheres reported in the literature [29][30][31][32][33][34].…”
Section: Resultssupporting
confidence: 71%
“…5a. According with Langmuir's isotherm an exponent n equal to 2 indicates that the adsorption of hydrogen is dissociative (i), which is consistent with studies of the hydrogen adsorption on Pt surfaces in dry atmospheres reported in the literature [29][30][31][32][33][34].…”
Section: Resultssupporting
confidence: 71%
“…The diffusion of atomic hydrogen into the subsurface of smooth, but not on defected, Pt(111) surfaces has been suggested experimentally [23,47] and theoretically [48,49].…”
Section: Introductionmentioning
confidence: 96%
“…Apparently, one can notice a systematic increase in the adsorption energy in the order of 0.08 eV as a function of increasing Pt/Au ratios having a lowest value of 0.43 eV corresponding to Au 201 H and a highest value of 1.11 eV corresponding to Pt 201 H. The adsorption energy obtained for Pt 201 H from this work is apparently higher (nearly three times) than that of the bridgePtPt site on a Pt111 surface reported in ref. 19. The experimental values of H adsorption on Pt111 scatters between 0.30 and 0.99 eV.…”
Section: (C) Adsorption Energiesmentioning
confidence: 99%